The Influence of Religious Coping and Religious Social Support on Health Behaviour, Health Status and Health Attitudes in a British Christian Sample - Brewer, Gayle (Journal of religion and health, 2015)
Previous research has established a relationship between religion and health. However, the specific aspects of religion which may influence health are not fully understood. The present study investigates the effect of religious social support and religious coping on health behaviours, health status and attitudes to health whilst controlling for age and non-religious social support. The results indicate religious coping and religious social support positively impact on self-reported current health status, depression, health outlook and resistance susceptibility. However, negative religious coping was predictive of increased alcohol consumption. Overall congregational support and negative religious coping had the greatest impact on health.